(untitled) (KULT_online, 2019)
In Das Sicherheitsdispositiv der Resilienz: Katastrophische Risiken und die Biopolitik vitaler Systeme, Andreas Folkers examines three fields of contemporary security-practices: German disaster control after 9/11, the protection of vital systems and critical infrastructures, and operative continuity-management. In how far, Folkers asks, does resilience function as a technology of rule and normative model for past and present security-practices. In identifying and exposing resilience as a security-dispositif, Folkers offers an insightful diagnosis of contemporary societies, the scope of which goes well beyond Germany and speaks to current debates in the field of critical security studies.